Isolated oligohydramnios: effects on obstetric and perinatal outcome - L., Ashwini Vishalakshi; P., Reddi Rani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Outcome of oligohydramnios has been studied at a large. Varying results have been projected in each study. This study has been done to establish the obstetric and perinatal outcome in pregnancy associated with oligohydramnios as compared to women with normal liquor. Methods: This was a prospective case controlled study done which included 100 women with oligohydramnios who were compared with 100 women with normal liquor. Maternal and perinatal outcome was compared between the two groups. Results: There was a significant difference in the obstetric and perinatal outcomes among the study and control groups. Significant variation was seen in the obstetric outcome with regards to the incidence of induction of labor and mode of delivery (by caesarean section). Both were increased among the study group as compared to the control group. CTG changes, meconium stained liquor, neonatal admissions and observations were more among the study group as compared to control group. Conclusions: Athough there is an increased rate of caesarean section, NICU admission and observation, thick meconium stained liquor and NST changes there is no significant increase in the perinatal morbidity and mortality.